2008
DOI: 10.1038/mt.2008.100
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and Selection of Shuffled AAV Genomes: A New Strategy for Producing Targeted Biological Nanoparticles

Abstract: We report a DNA shuffling-based approach for developing cell type-specific vectors through directed evolution. Capsid genomes of adeno-associated virus (AAV) serotypes 1-9 were randomly fragmented and reassembled using PCR to generate a chimeric capsid library. A single infectious clone (chimeric-1829) containing genome fragments from AAV1, 2, 8, and 9 was isolated from an integrin minus hamster melanoma cell line previously shown to have low permissiveness to AAV. Molecular modeling studies suggest that AAV2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
177
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(178 citation statements)
references
References 46 publications
1
177
0
Order By: Relevance
“…Intra-vitreous injection caused relatively little antibody production ( Figure 7a) compared with the different route of AAV injection used by Zhang et al 16 Li et al 40 demonstrated that a single intra-vitreous injection of AAV2 causes increased AAV antibody production at 2 months after injection. Our data are consistent with their report in terms of the timing of increase and the amount of antibody production (Figure 7a).…”
Section: Side Effect Of Channelrhodopsin-2 Gene Transfer E Sugano Et Almentioning
confidence: 90%
“…Intra-vitreous injection caused relatively little antibody production ( Figure 7a) compared with the different route of AAV injection used by Zhang et al 16 Li et al 40 demonstrated that a single intra-vitreous injection of AAV2 causes increased AAV antibody production at 2 months after injection. Our data are consistent with their report in terms of the timing of increase and the amount of antibody production (Figure 7a).…”
Section: Side Effect Of Channelrhodopsin-2 Gene Transfer E Sugano Et Almentioning
confidence: 90%
“…This understanding may further inform AAV vector technologies such as the use of rational capsid design or DNA shuffling to generate capsid mutants to escape antibody neutralization and enhance transduction. 37,38 One such mutant designed in our lab has been used in patients with Duchenne muscular dystrophy in a Phase I human clinical trial. 39 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Capsids of adeno-associated virus (AAV)-derived vectors have been modified for receptor targeting basically in three ways: (1) by conjugating receptorbinding ligands to their capsids, (2) by genetic insertion of ligands into the capsid (for reviews see Muzyczka and Warrington 1 and Buning et al 7 ) and (3) by DNA shuffling from different AAV serotypes. [8][9][10] Pseudotyping of AAV vectors with capsids of different serotypes also expanded the range of infectable cells, 11 but has not resulted in cell type-selective transduction after systemic application.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic modification of the AAV2 capsid by oligonucleotide insertions, random mutagenesis or DNA shuffling is able to circumvent some of these limitations. [8][9][10][17][18][19] Whereas larger peptides up to the size of GFP (238 amino acids) could be accommodated at the VP2 N-terminus 15,[20][21][22][23][24][25] the addition of small peptides up to 34 amino acids is tolerated at several positions of the AAV2 capsid. 1 Among the tolerated insertion sites for small peptides, insertions in the AAV2 heparin binding domain 26,27 adjacent to amino acids 587 or 588 was most successful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation